2011
DOI: 10.1088/0004-637x/729/1/28
|View full text |Cite
|
Sign up to set email alerts
|

Observational Constraints on Superbubble X-Ray Energy Budgets

Abstract: The hot, X-ray-emitting gas in superbubbles imparts energy and enriched material to the interstellar medium (ISM) and generates the hot ionized medium, the ISM's high-temperature component. The evolution of superbubble energy budgets is not well understood, however, and the processes responsible for enhanced X-ray emission in superbubbles remain a matter of debate. We present Chandra ACIS-S observations of two X-ray-bright superbubbles in the Large Magellanic Cloud (LMC), DEM L50 (N186) and DEM L152 (N44), wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 68 publications
4
48
1
1
Order By: Relevance
“…Moreover, the numerical models that appear in Jaskot et al (2011) produce luminosities that are two orders of magnitude lower than the observations (∼ 10 36 erg s −1 ). Therefore the authors explored the effect of the metallicity and of mass loading by clouds to bridge the luminosity deficit in soft X-rays.…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…Moreover, the numerical models that appear in Jaskot et al (2011) produce luminosities that are two orders of magnitude lower than the observations (∼ 10 36 erg s −1 ). Therefore the authors explored the effect of the metallicity and of mass loading by clouds to bridge the luminosity deficit in soft X-rays.…”
Section: Introductionmentioning
confidence: 79%
“…According to observations DM L152 has a radius of approximately 50 pc (Jaskot et al 2011), and DEM L50 has roughly the same radius (Oey 1996). Jaskot et al (2011) reported an X-ray luminosity in the range 2.0-4.0×10 36 erg s −1 for DEM L50 and an emission of 5.4-5.7×10 35 erg s −1 . These two superbubbles contrast with N70 and N185 in that they contain an off-centre SN explosion, which is clearly distinguishable in the observations.…”
Section: Comparisons With Observationsmentioning
confidence: 95%
See 3 more Smart Citations